FRI0339 Adherence To Vaccination and Osteoporosis Prevention in A French Systemic Lupus Erythematosus Cohort. (15th July 2016) - Scherlinger, M.; Hourdillé, A.; Pichon, C.; Schaeverbeke, T.; Viallard, J.-F.; Pellegrin, J.-L.; Lazaro, E.; Richez, C.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory disease in which improvements in treatments have led to new challenges in patient care. Longer survival and patients aging come with long-term complications that the rheumatologists should work to recognize and prevent effectively. In fact, osteoporosis and infections bear a great importance in disease-related morbidity, mortality and care-related costs of SLE patients. Objectives: Evaluate adherence to influenza and pneumococcal vaccination as well as to osteoporosis prevention in regard of the 2003 french recommendations, in a SLE patient cohort. Describe the factors associated with osteoporosis as well as with adherence to adequate vaccinal prevention. Methods: We included all SLE patients (fulfilling the American College of Rheumatology criteria), seen from May 2014 to November 2014, in Rheumatology or Internal medicine department from Bordeaux teaching hospital, France. Using 2 questionnaires and medical records, informations concerning patients, disease-related characteristics and adherence to preventions were collected. Statistical analyze was made with appropriate tests regarding the type of data and a p-value <0, 05 was considered of statistical significance. Results: One hundred and nine patients were included. There was 100 women (92%), mean disease duration was 9, 9 years. Renal and neurologic involvement were present in 20 and 9% of patients respectively. At the time of the study 76% were receiving hydroxychloroquine, 57% corticoids with 34% of them on a dose ≥7, 5mg prednisone/day and 57% had received an immunosuppressant. Twenty-one (19%) patients had an indication for anti-osteoporotic treatment. These patients were older (mean 54 versus 42 years, p<8.10 –4 ), had a longer use of corticosteroid (103.7 versus 62, 5 months, p<0.01) and a greater use of immunosuppressant (81% versus 51%, p<0.01). Lombar and femoral head T-score were negatively correlated with SLICC-ACR damage index after excluding fractures from the score (b = -0, 35 and -0, 27; p<0, 006 and p<0, 03 respectively). Only 12/21 (57%) patients received the indicated anti-osteoporotic treatment, mainly by lack of prescription by the attending physician. Only 11 patients (10%) received both influenza and pneumococcal vaccines, 35% received influenza vaccination at least once and 18% received pneumococcal vaccination. Reasons for non-vaccination were: lack of recommendation by general practitioner or rheumatologist (51%), fear of side effects (29%), contraindication with lupus (14%), inefficiency (2%). Predictive factors for an appropriate vaccination for both vaccines were: higher SLICC-ACR damage index (p<0, 03) and past or current treatment with rituximab (p<0, 02). Longer disease duration was associated with a better vaccination against influenza (p<0, 02), and contact with elderly for pneumococcal vaccine (p<0, 04). Conclusions: Osteoporosis treatment and infection prevention with influenza and pneumococcal vaccination remains low among SLE patients. Rheumatologists need to better implement these aspects in the global care of their SLE patients. Disclosure of Interest: None declared